Bus driver : factors that influences behaviour - Md Rohani, Munzilah (2013)
The behaviour of drivers is influenced by many factors, which include the personal characteristics, environmental and vehicle characteristics. Professional drivers, such as bus drivers, generally have higher levels of training and experience, and by virtue of their profession have attitudes, which are more likely to promote safe driving. However, bus drivers experience the same environmental traffic condition as other drivers, as well as additional constraints imposed by the vehicle characteristics, concern for passengers’ comfort/safety and the need to adhere to timetables. This paper reviewed these factors from previous researches.